Investigating the Mediating Effect of Customer Orientation Strategy on the Relationship between CRM Technology and Hotel Performance: The Case of Hotels in Malaysia - Mohammed, Abdulalem; Rashid, Basri; Tahir, Shahruddin (2017)
Although the concept of Customer Relationship Management (CRM) technology has been recognized as an important ingredient for business success, the relationship between CRM technology and organizations’ performance has been inconclusive and rarely examined in hotel industry in Malaysia. The aim of this study is to contribute to the research on CRM technology in hotel industry by examining the mediating role customer orientation strategy on the CRM-performance link.The study uses Partial Least Squares (PLS) to examine the data that were collected during the survey. The results reveal that CRM technology does not only affect hotel performance directly but also the CRM–hotel performance link is mediated by customer orientation strategy. Therefore, hotel managers should focus on customer orientation strategy to translate CRM technology to business outcomes.